Analisis Yuridis Terhadap Perkara Pemberhentian Tidak Dengan Hormat Anggota Polisi (Studi Putusan Nomor: 12/G/2022/PTUN.Srg) - Maharani Maharani; Sulasno Sulasno; Rokilah Rokilah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The State Administrative Court is a judicial institution that acts as a supervisor of government administration actions. The State Administrative Court, which is the court of first instance, has the function of examining, deciding, and resolving state administrative cases. One of the cases that falls into the realm of the State Administrative Court is the case of the Banten Regional Police Chief Decree Number: KEP/773/XI/2021 concerning the dishonorable dismissal from the Police service on behalf of Ara Syafana due to a violation of the Police professional code of ethics. This research aims to find out 1) The judge's consideration for determining decision number: 12/G/2022/PTUN.Srg with a case of dishonorable dismissal of a police officer, 2) Legal implications arising from decision number: 12/G/2022/PTUN.Srg. The use of qualitative research as a method of this research which type is normative juridical research and uses a case approach and statutory approach. In data collection techniques using literature studies with data acquisition from various related literature and regulations. The results of this study show that: 1) The entire lawsuit of the plaintiff was rejected by the Panel of Judges on the grounds that the arguments in the lawsuit filed by the plaintiff were not legally sufficient or the legal principles were incorrect and the truth of the arguments was not successfully proven by the plaintiff. 2) The legal implications arising from decision number: 12/G/2022/ PTUN.Srg have a significant impact, both for the plaintiff and for the Police institution. The decision resulted in the plaintiff losing his job as a police officer, losing his status as a police officer which could affect his legal rights and obligations. Of course, this also has an impact on the Police institution where the existence of this case can be a bad image of the police in the eyes of the public. This may affect confidence in the professionalism and integrity of the Police.